Production of cloned-caprine embryos in vitro obtained from interspecies nuclear transfer using bovine cytoplast and caprine karyoplast / Soh Hui Hui - Soh, Hui Hui (2012)
Production of cloned-caprine embryos using the intraspecies somatic cell nuclear transfer is limited by low source of caprine oocytes as the recipient cytoplast in Malaysia. Therefore, using the bovine oocytes as recipient cytoplast in interspecies somatic cell nuclear transfer is an alternative approach to produce large number of cloned-caprine embryos and subsequently offspring at a rapid rate. This study was aimed to produce cloned-caprine embryos in vitro by specifically evaluating the interspecies nuclear transfer technique such as enucleation methods, nuclear transfer methods and in vitro culture systems. Briefly, the bovine ovaries were collected from local abattoir and transported to the laboratory within 2 to 3 hours in saline solution (0.9% NaCl). Bovine oocytes were recovered by checkerboard slicing the entire surface of the ovary inside the culture dish by using the razor blade. Oocytes with several compact layers of cumulus cells were selected and cultured in in vitro maturation (IVM) medium for 20 to 22 hours. After maturation, cumulus oocyte complexes (COC) were denuded in hyaluronidase (0.1%) to remove the cumulus cells. The matured oocytes with extrusion of first polar body were selected for enucleation to remove the spindle. Caprine-foetal fibroblast cells (donor karyoplasts) were harvested and transferred into enucleated bovine oocytes. The reconstructed oocytes were activated and the reconstructed couplets were cultured in KSOM medium for in vitro embryos development in CO2 (5%) incubator at 38.5oC in humidified atmosphere for 8 days. The medium was changed every 2 days of in vitro culture. Samples of embryos from each stage were stained with Hoechst 33342 to examine the number of nuclei of the embryos. The data were presented as mean±SEM and were analysed using one-way ANOVA. The significant differences among treatments were further analysed by DMRT and P<0.05 was considered significant. ii In Experiment 1, two enucleation methods were compared, i.e. squeezing and aspiration. There was no significant difference in the percentages successfully enucleated oocytes (P>0.05) for both enucleation methods (squeezing vs. aspiration: 88.01±3.00% vs. 91.68±1.92%, respectively). In terms of manipulation efficiency, the duration needed to complete the enucleation together with injection, the speed for aspiration with sub-zonal injection was significantly faster (P<0.05) than squeezing with sub-zonal injection (41.18±2.77 and 83.82±3.16 minutes, respectively). In in vitro embryo development, the percent of cloned-caprine embryos from 2 cell stage up to blastocyst stage using squeezing (2 cell: 60.18±2.43%, 4 cell: 53.80±2.84%, 8 cell: 37.71±3.30%, morula: 24.45±2.71% and blastocyst: 12.08±2.95%) and aspiration (2 cell: 61.55±4.20%, 4 cell: 49.86±3.87%, 8 cell: 39.22±4.26%, morula: 21.07±3.94% and blastocyst: 10.93±1.87%) methods did not differ significantly (P>0.05). In Experiment 2, two nuclear transfer methods were compared, i.e. sub-zonal injection with electro-fusion and intracytoplasm injection. There were no significant differences (P>0.05) in the injection and reconstruction rates for both nuclear transfer methods. The percent cloned-caprine embryos obtained from interspecies SCNT at 2- and 8 cell using SUZI and ICI methods did not differ significantly (P>0.05). However, the percentages of cloned-caprine embryos at 4 cell, morula and blastocyst derived from SUZI method were significantly higher (P<0.05) compared to the ICI method (53.80±2.84% vs. 38.60±2.25%, 24.45±2.71% vs. 16.05±1.43% and 12.08±2.95% vs. 4.51±1.45%, respectively). In Experiment 3, three different in vitro culture system were compared, i.e. Group 1 (KSOM A throughout duration of the culture), observation of the embryos were recorded on days 3, 5, 7 and 8 without changing the medium; Group 2 (KSOM A on days 1-3, changed with KSOM A on days 3 and 5), the embryos were observed and recorded on days 3, 5, 7 and 8; and Group 3 (KSOM A on days 1-3, changed with iii KSOM B on days 3 and 5), the embryos were observed and recorded on days 3, 5, 7 and 8. Group 3 (2 cell: 60.18±2.43%, 4 cell: 53.80±2.84%, 8 cell: 37.71±3.30%, morula: 24.45±2.71% and blastocyst: 12.07±2.95%) showed significantly higher (P<0.05) in the in vitro development competence from 2 cell up to blastocyst stages compared to Groups 1 (2 cell: 49.01±2.02%, 4 cell: 36.92±3.02%, 8 cell: 26.46±1.74%, morula: 8.42±0.47% and blastocyst: 0.00±0.00%) and 2 (2 cell: 49.85±3.27%, 4 cell: 39.68±2.72%, 8 cell: 29.34±1.87%, morula: 10.22±1.49% and blastocyst: 0.00±0.00%). In Experiment 4, an attempt to produce pregnancy after oviduct embryo transfer of interspecies SCNT embryos and using ultrasound scanning for pregnancy diagnosis were carried out. A total of 63 cloned-caprine embryos were obtained from interspecies SCNT experiment. However, only 55 embryos of Grades 1 and 2 (4- and 8 cell stages) were chosen and transferred into 9 recipients with at least 1 CL. Unfortunately, after ultrasound scanning on day 30 of gestation age after embryo transfer, there was no pregnancy observed in the recipient goats after embryo transfer experiment. It can concluded from the present study that caprine embryos could be successfully produced through interspecies SCNT using caprine foetal fibroblast cell as donor karyoplast and bovine oocyte as recipient cytoplast under local setting in Malaysia. It is believe this is the first report of producing cloned-caprine embryos with satisfactory blastocyst rate in interspecies SCNT using KSOM supplementation additional of glucose. With this encouraging findings and future refined research, using caprine-bovine in interspecies SCNT to produce caprine embryos and offspring may offer a new approach to increase genetically superior goat population in Malaysia at a rapid rate to meet the goat meat and milk demand for the industry.